After Gezi: Moving towards post-hegemonic imagination in Turkey - (:unkn) unknown (My University, 2013)
This paper discusses the conflict between the AK Party government and the Gezi activism with reference to hegemony, power-resistance dichotomy, local/metanarratives and the carnivalesque. The AK Party's 11-year rule revolutionized center-periphery relations in Turkey. The party pioneered the democratization process until the 2011 elections but took an authoritarian turn afterwards -which gave rise to the revolts. However, the protests mobilized a heterogeneous group, some of whom maintained militarist and partiarchal metanarratives while others took a libertarian stance. This paper highlights the fragmentation of discourses under the "Gezi Spirit" as well as among AK Party supporters.